Agricultural innovations to scale up productivity and income from coconut farming - S, Anitha (Indian Farming, 2021)
Coconut sector has a huge potential for promoting innovations as it has rich resources of traditional indigenous knowledge. Research institutes over the years have developed and fine-tuned many innovations which include new technologies, machines and implements, new varieties, crop management practices, pest and disease management problems, agricultural labour problems. Timetested, rational and effective farmer practices suited to the local situations and local culture may be blended with modern crop production technologies, which in turn would promote sustainable coconut production. Innovative efforts should be continued for strengthening the transfer of technology and for improving productivity and profitability from coconut farming.